Local translatome sustains synaptic function in impaired Wallerian degeneration. - Paglione, M.; Restivo, L.; Zakhia, S.; Llobet Rosell, A.; Terenzio, M.; Neukomm, L.J. (EMBO Reports, 2025)
After injury, severed axons separated from their somas activate programmed axon degeneration, a conserved pathway to initiate their degeneration within a day. Conversely, severed projections deficient in programmed axon degeneration remain morphologically preserved with functional synapses for weeks to months after axotomy. How this synaptic function is sustained remains currently unknown. Here, we show that dNmnat overexpression attenuates programmed axon degeneration in distinct neuronal populations. Severed projections remain morphologically preserved for weeks. When evoked, they elicit a postsynaptic behavior, a readout for preserved synaptic function. We used ribosomal pulldown to isolate the translatome from these projections 1 week after axotomy. Translatome candidates of enriched biological classes identified by transcriptional profiling are validated in a screen using a novel automated system to detect evoked antennal grooming as a proxy for preserved synaptic function. RNAi-mediated knockdown reveals that transcripts of the mTORC1 pathway, a mediator of protein synthesis, and of candidate genes involved in protein ubiquitination and Ca[2+] homeostasis are required for preserved synaptic function. Our translatome dataset also uncovers several uncharacterized Drosophila genes associated with human disease. It may offer insights into novel avenues for therapeutic treatments.